2017
DOI: 10.3390/f8030068
|View full text |Cite
|
Sign up to set email alerts
|

Structure from Motion (SfM) Photogrammetry with Drone Data: A Low Cost Method for Monitoring Greenhouse Gas Emissions from Forests in Developing Countries

Abstract: Structure from Motion (SfM) photogrammetry applied to photographs captured from Unmanned Aerial Vehicle (UAV) platforms is increasingly being utilised for a wide range of applications including structural characterisation of forests. The aim of this study was to undertake a first evaluation of whether SfM from UAVs has potential as a low cost method for forest monitoring within developing countries in the context of Reducing Emissions from Deforestation and forest Degradation (REDD+). The project evaluated SfM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 52 publications
3
118
0
Order By: Relevance
“…Digital surface models (DSMs) and ultra-fine resolution orthophotos can be directly utilized to estimate tree heights and canopy size. Usually, these data are difficult to extract correctly because the height of a tree depends on site conditions (higher/lower stem density; [33]), decreased interpretation of surface area at dense forest sites [30], or even exposure to light and wind [34,35]. In addition, directly estimating parameters in lower layers, such as DBH (Diameter at Breast Height), from DSM or orthophotos is also difficult because of tree canopies, particularly in dense forest environments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Digital surface models (DSMs) and ultra-fine resolution orthophotos can be directly utilized to estimate tree heights and canopy size. Usually, these data are difficult to extract correctly because the height of a tree depends on site conditions (higher/lower stem density; [33]), decreased interpretation of surface area at dense forest sites [30], or even exposure to light and wind [34,35]. In addition, directly estimating parameters in lower layers, such as DBH (Diameter at Breast Height), from DSM or orthophotos is also difficult because of tree canopies, particularly in dense forest environments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this technique can be used to construct 3D models of an area through photogrammetry. This means that there are possibilities for extracting forest inventory data from UAS-sensed information [18,29,30,32]. Digital surface models (DSMs) and ultra-fine resolution orthophotos can be directly utilized to estimate tree heights and canopy size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress made in internal sensors, reduction of costs, more flexibility compared to spaceborne and airborne platforms, and precise GPS embedded are some of unique advantages that have enhanced the application of UAVs in a wide range of subjects. Recent studies have exhibited the feasibility of using UAVs in monitoring (Torres-Sanchez et al, 2015;Vega et al, 2015;Mlambo et al, 2017) and measurement of characteristics plant species (Chianucci et al, 2016;McNeil et al, 2016;Ivosevic et al, 2017). In contrary, relatively few investigations have studied the applicability of orthoimages taken by UAVs for mapping biophysical characteristics of trees and shrubs at single-tree levels.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies showed the full potential of these small and flexible platforms (f.e. Mlambo et al 2017). An overview is given in Colomina and Molina (2014).…”
Section: Introductionmentioning
confidence: 99%